Respuesta :

x

3

y

=

5

,  

x

+

5

y

=

3

Add  

3

y

to both sides of the equation.

x

=

5

+

3

y

x

+

5

y

=

3

Replace all occurrences of  

x

with the solution found by solving the last equation for  

x

. In this case, the value substituted is  

5

+

3

y

.

x

=

5

+

3

y

(

5

+

3

y

)

+

5

y

=

3

Solve for  

y

in the second equation.

Tap for more steps...

x

=

5

+

3

y

y

=

1

Replace all occurrences of  

y

with the solution found by solving the last equation for  

y

. In this case, the value substituted is  

1

.

x

=

5

+

3

(

1

)

y

=

1

Simplify  

5

+

3

(

1

)

.

Tap for more steps...

x

=

2

y

=

1

The solution to the system of equations can be represented as a point.

(

2

,

1

)

The result can be shown in multiple forms.

Point Form:

(

2

,

1

)

Equation Form:

x

=

2

,

y

=

1